2022
DOI: 10.1371/journal.pone.0278883
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical and radiological outcomes of percutaneous cervical nucleoplasty: A case–control study

Abstract: Background Percutaneous cervical nucleoplasty (PCN) is a simple, safe, and effective treatment for contained cervical herniated intervertebral disc (CHIVD). However, few studies have compared the actual benefits of PCN against conservative treatment (CT), either clinically or radiographically. Purpose The present study sought to analyze and to compare the outcomes of symptomatic contained CHIVD treated with PCN or CT. Methods The present study was designed as a case–control comparative study. Patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Furthermore, the patient's age is also a critical pathophysiological influencing factor. This is consistent with the mechanism of LNP, in which the younger and collage-richer the pulposus nucleus contained in the intervertebral disc, the more effective the disc coblation will be [36,46,47]. Compared to the radiomic features, the overall physiological parameters had a greater impact on building the ML models, which suggests that the AI-assisted image reading played the role of an assistant rather than a replacement.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the patient's age is also a critical pathophysiological influencing factor. This is consistent with the mechanism of LNP, in which the younger and collage-richer the pulposus nucleus contained in the intervertebral disc, the more effective the disc coblation will be [36,46,47]. Compared to the radiomic features, the overall physiological parameters had a greater impact on building the ML models, which suggests that the AI-assisted image reading played the role of an assistant rather than a replacement.…”
Section: Discussionsupporting
confidence: 74%
“…Cincu et al's report, based on 10 year follow-up data, concluded that LNP might provide intermittent pain relief in contained disc herniation without significant complications [35]. These differences between studies may be due to variability in patient selection and decision-making [36]. Based on the therapeutic methods of LDDD, Huo et al compared the efficacy between LNP and endoscopic discectomy and showed that LNP is more appropriate for young and middle-aged patients, a finding consistent with our results [37].…”
Section: Discussionmentioning
confidence: 99%
“…It uses a bipolar radiofrequency technology applied to a saline conducting medium, which vaporizes nuclear tissue, helping in the removal of herniated disc tissue. The primary disadvantage of the nucleoplasty device is the inability to access the herniated nucleus easily, limiting the direct removal of herniated disc tissue [ 1 , 2 ]. A new navigable percutaneous disc decompressor (L’DISQ-C, U&I Co., Uijeongbu, Korea), introduced in 2012, is designed to allow direct access to herniated disc material.…”
Section: Introductionmentioning
confidence: 99%